Exploring class identification among Finnish party members - Tiihonen Aino; Koivula Aki; Saarinen Arttu; Sivonen Jukka (Wiley, 2025)
Class cleavage has been an important factor in forming the West-European party systems, and class identification can still be considered one of the key types of social identity, especially among members of older parties. Nevertheless, previous research has ignored the importance of party members' class identifications. In this study, we hypothesise that party affiliation can form a context of social identity in which party members' class identification is also strengthened. By analysing unique survey data of 12,427 members of the six largest Finnish parties, we examine the extent to which party members' class identifications stem from their party affiliations and how the relationship is reinforced by their partisan identity. The results suggest that traditional class-cleavage elements still appear within class identification among the members of older parties. Members of left-wing parties identified with the working class, and conversely, upper-class identification was more prominent among members of centre-right parties. Among members of newer political parties, the class was less relevant compared to members of traditional class-based parties. Furthermore, we found that working-class identification was strongly related to the strength of partisan identity.